Shell structures in civil and mechanical engineering theory and closed-form analytical solutions - Zingoni, Alphose (London Thomas Telford, 1997)
This book explains, in a practical and straightforward way, the fundamental theory needed to understand the behaviour and analysis of a wide range of shell structures within the industry. It provides explanations of both the membrane and bending theories of shells; provides general solutions to specific types of problems encompassing pressure vessels, pipes, liquid-retaining tanks, cooling towers, domes and shells roofs; derives the results for junction problems of many shell structures (including those of compound geometry), and presents these in simple closed-form format for the convenience of the practical analyst and designer; and employs comprehensive parametric studies based on the closed-form analytical results, to propose useful design recommendations for a variety of shell structures.
Includes index
Keywords: Shells (Engineering)